Peristaltic transport of a maxwell fluid in a channel of varying cross section induced by asymmetric waves: Application to embryo transport within uterine cavity - Pandey S.K.; Chaube M.K. (My University, 2025)
This is an attempt to analyze the peristaltic flow of a Maxwell fluid in a tapered channel. Peristaltic wave trains with different amplitudes and phases are considered to propagate along the two walls of the channel producing asymmetric wall movements. A perturbation technique is employed to solve the problem by giving due consideration to the non-linear convective acceleration terms in the analysis. The effects of the non-Newtonian parameters relaxation time, angle of inclination between channel walls, and phase difference on the mean flow velocity are analyzed. It is found that the mean axial velocity decreases with relaxation time, phase difference, and the angle between the channel walls. Moreover, the value of the mean axial velocity is found to be less with asymmetric waves as compared with symmetric waves. © 2011 World Scientific Publishing Company.